(untitled) - Rogmans, Tim (Business Expert Press, 2012)
Ebook from IG Library ; Over the next decade, the economies of the Middle East will continue to be characterized by rapid growth, political turmoil, and increasing competitive intensity. International investors have the choice of either ignoring the region all together and bypassing business opportunities with great potential, or to make a careful assessment of which countries to enter and how to enter them successfully. This book is the first of its kind to include the information, insights and frameworks that are required to develop entry and growth strategies for the Middle East in the new turbulent environment following the global economic crisis and the Arab Spring. The first part of the book provides an in-depth analysis of the major developments that determine the business environment of different countries in the region, including a discussion of major social and economic developments, the impact of the rise multinational companies from the Middle East, and the role played by institutions and political risk. The second part deals with each of the major decisions that a company planning to grow in the region needs to make: Which countries to enter? What is the right entry mode and ownership structure? How to choose between a Greenfield operation and an acquisition? The book concludes valuable and practical advice on the process of setting up operations in the Middle East.
Keywords: Kinh doanh quốc tế; International Business